Evaluation of the influence of physical activity on the plasma concentrations of several trace metals - Rodriguez, T. I; Pinilla, G. E.; Maynar, M. M.; Garcia-Monco, C. R.; Sanchez, M. A. (European Journal of Applied Physiology, 1996)
Our study was carried out with the aim of evaluating the influence that the degree of physical activity may have on plasma concentrations of essential and toxic elements. Copper and zinc, elements of known importance in basic cellular processes, have been analysed as essential, and cadmium and lead as toxic for the body in abnormal doses. The study was performed on a total population of 50 healthy individuals, 34 of them professional sportsmen and the rest who undertook moderate physical activity (control group), all of them living in a polluted environment (Madrid, Spain). Sampling was conducted at the beginning of the season (October). Electro-analytical techniques of proved reliability and accuracy were used for the determination of the metals. The results were related to data obtained using graphite furnace atomic absorption spectrophotometry and by use of biological reference materials. We found significantly higher zinc plasma concentrations in the sportsmen involved in anaerobic-type training (judo, fencing) compared to those undertaking aerobic activities (endurance, cycling) (P < 0.05). The values in both cases were higher than those found in the control group. Our study showed an increase of plasma copper concentrations in professional sportsmen, especially in those performing anaerobic activities, compared to those subjects undertaking moderate activity (control group) (P < 0.05). In summary, our results showed that there were no deficiencies of copper and zinc in the athletes studied at the beginning of the season. The levels were higher than those of the control population. As for the toxic metals, cadmium and lead, we observed lower levels in the athletes than in the control group (cadmium P < 0.005, lead P < 0.05). These results may indicate the existence of possible elimination systems for these metals in athletes, when they are training in a polluted environment.